Pathological Functions of LRRK2 in Parkinson’s Disease - Ga Ram Jeong; Byoung Dae Lee (Cells, 2020)
Mutations in the gene encoding leucine-rich repeat kinase 2 (LRRK2) are common genetic risk factors for both familial and sporadic Parkinson’s disease (PD). Pathogenic mutations in LRRK2 have been shown to induce changes in its activity, and abnormal increase in LRRK2 kinase activity is thought to contribute to PD pathology. The precise molecular mechanisms underlying LRRK2-associated PD pathology are far from clear, however the identification of LRRK2 substrates and the elucidation of cellular pathways involved suggest a role of LRRK2 in microtubule dynamics, vesicular trafficking, and synaptic transmission. Moreover, LRRK2 is associated with pathologies of α-synuclein, a major component of Lewy bodies (LBs). Evidence from various cellular and animal models supports a role of LRRK2 in the regulation of aggregation and propagation of α-synuclein. Here, we summarize our current understanding of how pathogenic mutations dysregulate LRRK2 and discuss the possible mechanisms leading to neurodegeneration.